Ammonium fertilization increases the susceptibility to fungal leaf and root pathogens in winter wheat - Maywald, Niels Julian; Mang, Melissa; Pahls, Nathalie; Neumann, Günter; Ludewig, Uwe; Francioli, Davide (Frontiers in Plant Science, 2022)
Nitrogen (N) fertilization is indispensable for high yields in agriculture, due to its central role in plant growth and fitness. Different N forms affect plant defence against foliar pathogens and may alter soil-plant-microbe interactions. To date, however, the complex relationships between N forms and host defence are poorly understood. For this purpose, nitrate, ammonium, and cyanamide were compared in greenhouse pot trials with the aim to suppress two important fungal wheat pathogens Blumeria graminis f. sp. tritici (Bgt) and Gaeumannomyces graminis f. sp. tritici (Ggt). Wheat inoculated with the foliar pathogen Bgt was comparatively up to 80 % less infested when fertilized with nitrate or cyanamide than with ammonium. Likewise, soil inoculation with the fungal pathogen Ggt revealed a 38 % higher percentage of take-all infected roots in ammonium-fertilized plants. The bacterial rhizosphere microbiome was little affected by the N form, whereas the fungal community composition and structure were shaped by the different N fertilization, as revealed from metabarcoding data. Importantly, we observed a higher abundance of fungal pathogenic taxa in the ammonium-fertilized treatment compared to the other N treatments. Taken together, our findings demonstrated the critical role of fertilized N forms for host-pathogen interactions and wheat rhizosphere microbiome assemblage, which are relevant for plant fitness and performance.